Reform of Corruption Criminal Law: a Study of Corruptor Asset Application Law in Indonesia - Achmad Taufan Soedirjo; Faisal Santiago; Surya Jaya (International Journal Labs, 2023)
The development of a new criminal law system in Indonesia still aims to reveal the crimes committed, find the perpetrators, and punish them with criminal sanctions, especially